Port Of The Inland Waterways - Argo Victoria Ong (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
Inland water harbor is a port located in the inland waters of a large river that can be navigated, canal / river or in a lake. The inland port can function like a seaport with various loading and unloading activities including container ships, tankers, roro ships and so on like the Boom Baru port in Palembang, Trisakti Port located in the suburbs of Banjarmasin, the capital of South Kalimantan Province, is located on the banks of the Barito River, about 20 miles from the mouth of the Barito River at position 03